No place to hide as DNS comes under attack. Issue 7 (July 2016) - Murphy, Malcolm
Abstract : It is commonly assumed that most cyber-attacks originate from hotspots in Eastern Europe, Southeast Asia and Africa, where infrastructure is not especially well policed. However, recent analysis demonstrates that the majority of the underlying infrastructure used to launch these attacks lies safely and comfortably in some of the world's most developed countries. 1 This is according to the latest DNS Threat Index which found that the US and Germany account for more than 90% of malicious infrastructure created from October to December 2015. Recent analysis demonstrates that the majority of the underlying infrastructure used to launch cyber-attacks lies in some of the world's most developed countries, exploiting weaknesses in DNS technology. As a vital component of network architecture, DNS should not be overlooked and left unprotected. By employing intelligence on the types of threats facing their DNS infrastructure and taking the steps necessary to impede malicious domains, organisations can take control of their DNS, transforming it into a source of security, says Dr Malcolm Murphy of Infoblox.